Are self-ligating brackets related to less formation of Streptococcus mutans colonies? A systematic review - Leonard Euler Andrade Gomes do Nascimento; Margareth Maria Gomes de Souza; Angela Rita Pontes Azevedo; Lucianne Cople Maia (Dental Press Journal of Orthodontics, 2014)
OBJECTIVE: To verify, by means of a systematic review, whether the design of brackets (conventional or self-ligating) influences adhesion and formation of Streptococcus mutans colonies. METHODS: Search strategy: four databases (Cochrane Central Register of Controlled Trials, Ovid ALL EMB Reviews, PubMed and BIREME) were selected to search relevant articles covering the period from January 1965 to December 2012. Selection Criteria: in first consensus by reading the title and abstract. The full text was obtained from publications that met the inclusion criteria. Data collection and analysis: Two reviewers independently extracted data using the keywords: conventional, self-ligating, biofilm, Streptococcus mutans, and systematic review; and independently evaluated the quality of the studies. In case of divergence, the technique of consensus was adopted. RESULTS: The search strategy resulted in 1,401 articles. The classification of scientific relevance revealed the high quality of the 6 eligible articles of which outcomes were not unanimous in reporting not only the influence of the design of the brackets (conventional or self-ligating) over adhesion and formation of colonies of Streptococcus mutans, but also that other factors such as the quality of the bracket type, the level of individual oral hygiene, bonding and age may have greater influence. Statistical analysis was not feasible because of the heterogeneous methodological design. CONCLUSIONS: Within the limitations of this study, it was concluded that there is no evidence for a possible influence of the design of the brackets (conventional or self-ligating) over colony formation and adhesion of Streptococcus mutans.